La folie de l’arc-en-ciel ou la longue errance de Bwila - Claudie Haxaire (Revue d'ethnoécologie)
The Guro people in the Guo territorial unit in Ivory Coast practice a divination dance called Dawa, which we analysed in detail. This dance has the value of a therapeutic ritual for the novice: the success of the dance, i.e. full restitution of the word of the oracle, is a sign of mastery of communication with the tutelary ancestors (“zu”) and thus of the possession of sufficient might to resist the specific madness – “zu madness” – that they would otherwise provoke. The meaning of this ritual and the progression of the healing process can indeed be deduced from the Guro vision of the world and from the Guro notion of a person. However, the glosses given by exegetes must be examined in the light of an analysis of practices, in other words, the scenogram: staging of the actors taking part in the ritual, exchange of powerful objects between the actors, ritual acts and gestures. The handling of plants and the ingestion of remedies must not be overlooked, even though these take on meaning only in the context of the encyclopedic knowledge of the population group that practices the ritual, knowledge that must be acquired. In the present case, the analysis of the medicinal formulas prescribed to treat “zu madness” among the Guro of the Ivory Coast, set in the overall context of medicinal treatment for madness in general, enables us to outline the “organisational principles” as defined by Loux and Saillant (1990). This analysis serves as a validation, confirmation or criticism – via the practices – of the interpretations drawn from interviews and observations of illness episodes and of therapeutic rituals presented beforehand. The study of traditional pharmacopoeias, restored in the full scope of their organisation, provides a privileged empirical context to fully understand the meaning of ritual symbols whose different facets need to be deployed, according to Turner (1968). It is unfortunate that, like Evans-Pritchard ([1931] 1972), many anthropologists who work on misfortune and illness, and all the more on rituals, did not seek further details of the material or symbolic properties of plants used by healers while following their interlocutors.